Quantitative Assessment of Hand Spasticity After Stroke: Imaging Correlates and Impact on Motor Recovery - Plantin, Jeanette; Pennati, Gaia V.; Roca, Pauline; Baron, Jean-Claude; Laurencikas, Evaldas; Weber, Karin; Godbolt, Alison K.; Borg, Jörgen; Lindberg, Påvel G. (Frontiers in Neurology, 2019)
Objective: This longitudinal observational study investigated how neural stretch-resistance in wrist and finger flexors develops after stroke and relates to motor recovery, secondary complications and lesion location. Methods: Sixty-one patients were assessed at three weeks (T1), three (T2) and six months (T3) after stroke using the NeuroFlexor method and clinical tests. Magnetic Resonance Imaging was used to calculate weighted corticospinal tract lesion load (wCST-LL) and to perform voxel-based lesion symptom mapping. Results: NeuroFlexor assessment demonstrated spasticity (neural component [NC] >3.4N normative cut-off) in 33% of patients at T1 and in 51% at T3. Four subgroups were identified: early Severe spasticity (n = 10), early Moderate spasticity (n = 10), Late developing spasticity (n = 17) and No spasticity (n = 24). All except the Severe spasticity group improved significantly in Fugl-Meyer Assessment (FMA-HAND) to T3. The Severe and Late spasticity groups did not improve in Box and Blocks Test. The Severe spasticity group showed a 25° reduction in passive range of movement and more frequent arm pain at T3. wCST-LL correlated positively with NC at T1 and T3, even after controlling for FMA-HAND and lesion volume. Voxel-based lesion symptom mapping showed that lesioned white matter below cortical hand knob correlated positively with NC. Conclusion: Severe hand spasticity early after stroke is negatively associated with hand motor recovery and positively associated with the development of secondary complications. Corticospinal tract damage predicts development of spasticity. Early quantitative hand spasticity measurement may have potential to predict motor recovery and could guide targeted rehabilitation interventions after stroke.